NILAI KARAKTERISTIK PULAU DOMPAK SEBAGAI â€œCITRA PUSAT PEMERINTAHAN PROVINSI KEPULAUAN RIAUâ€ DI KOTA TANJUNGPINANG - Hari Dewi Purwasih; Wartono Wartono; Edi Indera (Universitas Batam, 2021)
Tanjungpinang City is an autonomous city that was formed in 2004 and designated as the Capital of the Riau Islands Province. The development of Tanjungpinang City has been growing rapidly since the construction of the Riau Islands Province government center, which is located on Dompak Island. The development resulted in rapid changes in land use, so that the fulfillment of urban facilities and infrastructure was needed to support all activities that were developing and to improve services for activities that already existed. Dompak Island can be a micro-economic commodity for local residents by considering that Dompak Island has adequate facilities, there are universities, Grand Mosques, beaches, historical sites, interesting spots according to Malay culture.